Sink or Swim: In Search of a Model for Coastal City Climate Resilience - Adams-Schoen, Sarah J. (Columbia Journal of Environmental Law, 2019)
Although the threats of global climate change are by no means limited to coastal areas, coastal cities face extreme and unique challenges. Global temperatures are increasing and the rate of increase is accelerating-with corresponding increases in sea levels, acidification of oceans, and losses of flood-mitigating wetlands. Storms and other extreme weather events are increasing in frequency and severity. As a result, coastal communities are already experiencing rising sea levels, eroding shores, more massive storm surges, more severe storms, salt water intrusion, loss of land and changes in marine resources -and all cities can expect increased incidences of, and more extreme, storms, heat waves, droughts, and other extreme weather conditions. ... New York City is on a short list of U.S. cities that began proactively planning for future climate-change related risks in the early 2000s. Since then, the city has assessed its vulnerabilities, planned for, and, significantly, begun implementing extensive mitigation and adaptation initiatives....Given the robustness of New York City's approach as well as the need for "high adaptation" of coastal cities, municipalities across the United States, and coastal cities in particular, can benefit from examining New York City's strategies, successes, and lessons learned. As discussed below, many of New York City's climate change measures have put the City in a league of its own, contributing significantly to the City's resilience, decreasing GHG emissions, and providing significant co-benefits like improved public health, cleaner air and, according to the City, more affordable housing. But, the City also faces a host of challenges that threaten to "sink" it, including wicked policy binds, ineffective regional structures, a lack of support at the federal level, and other conditions that constrain the City's ability to remain resilient such as its massive population, coastal geography, and increasingly frequent and intense coastal storms, storm surges, and flooding. As a result, the City's climate change resilience initiatives may still fall short of what is required to sufficiently "moderate[] harm" from dangerous interference with the climate system.